2006
DOI: 10.1111/j.1460-9568.2006.04603.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of conditioned fear extinction by infusion of the GABAA agonist muscimol into the rat prefrontal cortex and amygdala

Abstract: In auditory fear conditioning, repeated presentation of the tone in the absence of the shock leads to extinction of the acquired fear response. Both the infra limbic prefrontal cortex (IL) and the basolateral amygdala (BLA) are involved in extinction. In this study, we examine the involvement of these two regions in extinction by manipulating the gamma-aminobutyric acid (GABA)ergic system, in the Sprague-Dawley rat. We microinfused a low dose of the GABA(A) agonist muscimol into the IL or BLA. Muscimol infused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(122 citation statements)
references
References 60 publications
9
111
1
1
Order By: Relevance
“…Perhaps consistent with this idea, Morgan et al 155 reported that PFC lesions had no effect on an initial extinction training session when administered postacquisition, but did impair the rate of re-extinction following reacquisition when these phases of training were done with the lesions already in place. On the other hand, studies employing inactivation of mPFC via infusion of GABA receptor agonists before extinction training or test have reported either no effect (KM Myers and M Davis, unpublished data) or facilitation of extinction, 94 contrary to the predictions of the prefrontal model. It is not clear at the present time how to interpret these inconsistencies.…”
Section: Neural Mechanismsmentioning
confidence: 91%
See 2 more Smart Citations
“…Perhaps consistent with this idea, Morgan et al 155 reported that PFC lesions had no effect on an initial extinction training session when administered postacquisition, but did impair the rate of re-extinction following reacquisition when these phases of training were done with the lesions already in place. On the other hand, studies employing inactivation of mPFC via infusion of GABA receptor agonists before extinction training or test have reported either no effect (KM Myers and M Davis, unpublished data) or facilitation of extinction, 94 contrary to the predictions of the prefrontal model. It is not clear at the present time how to interpret these inconsistencies.…”
Section: Neural Mechanismsmentioning
confidence: 91%
“…In contrast, Berlau and McGaugh 96 reported no effect of unilateral (right) BLA infusions (cf. Lalumiere and McGaugh 97 ) of muscimol immediately after extinction training upon extinction of contextual freezing, even with a dose of muscimol that was considerably higher than that employed by Akirav 94 (125 vs 50 ng). Moreover, contrary to what one would have expected from Akirav, 94 Berlau and McGaugh 96 reported facilitation of extinction retention by unilateral infusions of the GABA A receptor antagonist bicuculline (which would be expected to increase amygdalar activity) into the right BLA immediately, but not 3 h, following extinction training.…”
Section: Neural Mechanismsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover; depending on the duration of the reactivation trial, the emergence of reconsolidation or the consolidation of extinction requires a reduced GABAergic neurotransmission. Previous reports (Pereira et al, 1989;Akirav et al, 2006;Akirav, 2007) have also shown that GABA-A agonist or diazepam administration, another BDZ compound, interrupted the fear extinction memory using different learning memory tasks, and McGaugh et al (1990) show that the administration of GABA-A receptors antagonist enhances extinction during testing. However, Harris and Westbrook (1998, 2001 propose that GABA neurotransmission facilitates the acquisition and expression of extinction.…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition, GluR5 is presynaptically present in GABA neurons, modulating the release of GABA in a dose-dependent, bidirectional manner. 24 A low concentration of glutamate, as well as basal activity, facilitates the release of GABA, but high levels of glutamate suppress GABA release from the interneuron to pyramidal cells in the basolateral amygdala. 24 Topiramate's inhibition of GluR5 may allow the release of GABA even with high glutamate activity.…”
Section: Figmentioning
confidence: 99%